Surviving suicide loss : making your way beyond the ruins - Schulte, Rita A. (Northfield Publishing, 2021)
"If you are struggling with suicide loss or you need to come alongside someone who is, Rita Schulte wants to help. As a suicide loss survivor, she understands the pain because she has been there too. Her science-based therapy model that takes human spirituality into account offers hope"--